2021
DOI: 10.1007/s11682-021-00459-y
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem substructures and cognition in prodromal Alzheimer’s disease

Abstract: Neuropathological research suggests the tau pathology of Alzheimer’s disease may originate in brainstem nuclei, yet it remains unknown whether tau-mediated degeneration of brainstem nuclei influences cognitive impairment in prodromal Alzheimer’s disease. The present study examined cognitive domains impacted in prodromal Alzheimer’s disease and brainstem substructure volume in cognitively normal older adults (n = 814) and those with mild cognitive impairment (n = 542). Subsamples of cognitively normal (n = 112)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
(85 reference statements)
2
21
0
Order By: Relevance
“…However, education level did show a positive association with overall brain volume (in the HC and MCI groups) suggesting it might be more closely associated with brain development and expansion rather than later life brain maintenance. Few studies have investigated the relationship between LC volume and attentional performance in older adults [48,55,33]. The present study utilised the Trail Making Test A (TMT-A) as a putative measure of visual attention speed, and found that greater LC volume in MCI and AD patients was associated with faster attention performance.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, education level did show a positive association with overall brain volume (in the HC and MCI groups) suggesting it might be more closely associated with brain development and expansion rather than later life brain maintenance. Few studies have investigated the relationship between LC volume and attentional performance in older adults [48,55,33]. The present study utilised the Trail Making Test A (TMT-A) as a putative measure of visual attention speed, and found that greater LC volume in MCI and AD patients was associated with faster attention performance.…”
Section: Discussionmentioning
confidence: 90%
“…First, to examine the relationship between LC integrity and cognitive function measured by the Trail Making Test A (TMT-A), which is a clinical tool sensitive to basic attentional efficiency, visual search and motor processing speed. We anticipated that greater LC integrity would be negatively associated with TMT-A completion time in seconds, according to previous findings [29,48,55] and consistent with Robertson's theory [1,2]. TMT part A has been chosen over the part B since the latter was not completed by all the selected participants included in the ADNI (specifically in the Alzheimer's group), and also because it is considered to evaluate more structured cognitive processes such as cognitive flexibility and divided attention [75,76].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To this end, we adopted a neuroimaging voxel-based morphometry (VBM) approach utilizing 3T T1-weighted structural MRI scans from 686 subjects [n=395 (HC), n=156 (MCI), and 135 (AD)] provided by Alzheimer's Disease Neuroimaging Initiative -ADNI (ADNI2 and ADNI3 phases) [49,50]. Structural volumetric analyses on 3T T1-weighted MRIs with this methodology have been already carried out by several studies showing accurate reliability investigating the integrity of the Brainstem [51,52,53,54], the LC also in the ADNI [55,56,57,58] and the other neuromodulators' seeds such as the Raphe Nuclei [59,60,61,62], the Ventral Tegmental Area (VTA) [63,64,65,66] and the Nucleus Basalis of Meynert (NBM) [67,68,69,70,71,72,73,74]. The main objectives of this study were threefold.…”
Section: Introductionmentioning
confidence: 99%
“…First (1 st branch of VBM analyses), to examine the relationship between LC integrity and cognitive function measured by the Trail Making Test A (TMT-A), which is a clinical tool sensitive to basic attentional efficiency, visual search and motor processing speed [79,169,170]. We anticipated that greater LC volume would be negatively associated with TMT-A completion time in seconds, according to previous findings [29,48,55] and consistent with Robertson's theory [1,2]. TMT part A has been chosen over the part B since the latter was not completed by all the selected participants included in the ADNI (specifically in the Alzheimer's group), and also because it is considered to evaluate more structured cognitive processes such as cognitive flexibility and divided attention [75,76].…”
Section: Introductionmentioning
confidence: 99%